International workshop on insecticide resistance in vectors of arboviruses, December 2016, Rio de Janeiro, Brazil - Corbel, Vincent (2018)
Vector-borne diseases transmitted by insect vectors such as mosquitoes occur in over 100 countries and affect almost half of the world’s population. Dengue is currently the most prevalent arboviral disease but chikungunya, Zika and yellow fever show increasing prevalence and severity. Vector control, mainly by the use of insecticides, play a key role in disease prevention but the use of the same chemicals for more than 40 years, together with the dissemination of mosquitoes by trade and environmental changes, resulted in the global spread of insecticide resistance. In this context, innovative tools and strategies for vector control, including the management of resistance, are urgently needed. This report summarizes the main outputs of the first international workshop on Insecticide resistance in vectors of arboviruses held in Rio de Janeiro, Brazil, 5-8 December 2016. The primary aims of this workshop were to identify strategies for the development and implementation of standardized insecticide resistance management, also to allow comparisons across nations and across time, and to define research priorities for control of vectors of arboviruses. The workshop brought together 163 participants from 28 nationalities and was accessible, live, through the web (> 70,000 web-accesses over 3 days).